Effects of SGLT2 Inhibitors and DPP-4 Inhibitors on Advanced Glycation End Products - Kusunoki, Masataka; Hisano, Fumiya; Matsuda, Shin-ichi; Kusunoki, Akiko; Abe, Tomokazu; Tsutsumi, Kazuhiko; Miyata, Tetsuro (Drug Research, 2024)
Clinical trials have revealed that sodium glucose cotransporter 2 (SGLT2) inhibitors suppress the onset of heart failure and cardiovascular death in diabetic patients. On the other hand, few reports have been published concerning such effects of dipeptidyl peptidase-4 (DPP-4) inhibitors. We undertook the present study to evaluate the effects of SGLT2 inhibitors and DPP-4 inhibitors on the advanced glycation end products (AGEs), well known as a risk factor for the development of cardiovascular disorders.Type 2 diabetes mellitus were divided into two groups and treated with either SGLT2 inhibitors or DPP-4 inhibitors for 3 months. Before and after the 3-month treatment period with each drug, the AGEs and diabetes-related parameters were measured. Methylglyoxal-derived hydroimidazolone-1 (MG-H1) was measured as one of the AGEs.In the SGLT2 inhibitor group, both the blood HbA1c and MG-H1 levels decreased significantly after the 3-month treatment period. In the DPP-4 inhibitor group, only the blood HbA1c level decreased significantly, with no significant change of the blood MG-H1 level.SGLT2 inhibitor reduced both the blood levels of HbA1c and AGEs (MG-H1). Considering that the blood levels of AGEs are associated with the risk of heart failure and cardiovascular disorders, the results of the present study suggest that the effect of SGLT2 inhibitors in suppressing cardiovascular death might be mediated by the reduction in the blood levels of AGEs induced by this class of drugs. DPP-4 inhibitors showed no significant effects on the blood levels of AGEs.
Keywords: SGLT2 inhibitor; DPP-4 inhibitor; advanced glycation end products; MG-H1; type 2 diabetes mellitus